2012
DOI: 10.4028/www.scientific.net/kem.510-511.406
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of the Mustard Methyl Esters

Abstract: Mustard Methyl Esters (further biodiesel) and regular diesel fuel were tested in direct injection diesel engine. Analysis of experimental data was supported by an analysis of fuel injection and combustion characteristics. Engine fuelled with biodiesel had increased brake specific fuel consumption, reduced nitrogen oxides emission and smoke opacity, moderate increase in carbon monoxide emission with essentially unchanged unburned hydrocarbons emission. Increase in fuel consumption was attributed to lesser heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“… Biodiesel feedstock Engine Operating Condition Emission Results References Mustard oil methyl ester BD Horizontal, 1-cylinder, 4-stroke, AC, DI 1-Cylinder, 4-stroke, WC, RP: 5HP, RS: 1500 rpm 2200 rpm and 1 kg load is used. At different engine load and fuel blend Lower all HC, PM, NO X emissions with fuel blend Decreases HC, CO 2 , emission with an increase in fuel blend and increase in NO x Bannikov and Vasilev (2012) MY Cotton seed oil methyl ester BD 1-Cylinder, WC, NA, 4 stroke, DI 1-cylider, 4S, DI, NA, D: 553 cm 3 , RP: 4.476 kW, RS: 1800 rpm 1100–1800 rpm Different speeds and different blends 9 (B10, B20, B30) 1000–1600 rpm and full load CO, PM, Smoke emission reduced, NO x increased 10% increase in NO x and lower CO, 24%PM, 14% smoke compare with diesel fuel. Nabi et al.…”
Section: Sustaining Covid-19 Era Lockdown Environment Through Renewable Energy Resourcesmentioning
confidence: 97%
“… Biodiesel feedstock Engine Operating Condition Emission Results References Mustard oil methyl ester BD Horizontal, 1-cylinder, 4-stroke, AC, DI 1-Cylinder, 4-stroke, WC, RP: 5HP, RS: 1500 rpm 2200 rpm and 1 kg load is used. At different engine load and fuel blend Lower all HC, PM, NO X emissions with fuel blend Decreases HC, CO 2 , emission with an increase in fuel blend and increase in NO x Bannikov and Vasilev (2012) MY Cotton seed oil methyl ester BD 1-Cylinder, WC, NA, 4 stroke, DI 1-cylider, 4S, DI, NA, D: 553 cm 3 , RP: 4.476 kW, RS: 1800 rpm 1100–1800 rpm Different speeds and different blends 9 (B10, B20, B30) 1000–1600 rpm and full load CO, PM, Smoke emission reduced, NO x increased 10% increase in NO x and lower CO, 24%PM, 14% smoke compare with diesel fuel. Nabi et al.…”
Section: Sustaining Covid-19 Era Lockdown Environment Through Renewable Energy Resourcesmentioning
confidence: 97%
“…In contrast, the average BSFC for MB10 and MB20 were found to be 9% and 12% higher, respectively, than that of diesel fuel. Bannikov et al 19 also found a similar higher BSFC for mustard biodiesel over diesel fuel. This amount for CB10 and CB20 were found to be 6% and 10% higher, respectively, than that of diesel fuel.…”
Section: Prediction Of Blend Propertiesmentioning
confidence: 76%
“…14 Fig. Bannikov et al 19 also found a similar higher BSFC for mustard biodiesel over diesel fuel. It was observed that the BSFC of biodiesel is generally higher compared to that of diesel fuel.…”
Section: Performance Analysismentioning
confidence: 83%
“…Due to having a lower heating value, biodiesel and its blends release less heat during combustion, and thus to provide the same amount of power needs more fuel to be injected, thus increasing BSFC [130]. On the contrary, a study reported that biodiesel decreased BSFC and increases BTE [131] and CO, HC, and PM emissions and decreases NO X emission [104,[132][133][134][135][136]. Biodiesel is more oxygenative and it causes enhanced corrosion and material degradation [137][138][139].…”
Section: Biodiesel As a Diesel Substitutementioning
confidence: 99%